Pemanfaatan Onggok Fermentasi (Casapro) Terhadap Keempukan Daging Itik Pedaging - Kaffi, Suraya; Zairiful, Zairiful; Zulfahmi, Zulfahmi (Politeknik Negeri Lampung., 2013)
Duck meat has a fishy smell weakness, tough and a higher fat content, but it has the advantage of a high content of protein and low in calories. Factors that cause the meat is that it contains a lot of connective tissue protein, collagen has a structure that is very complex and overlap. Factors that cause the meat is that it contains a lot of connective tissue protein, collagen has a structure that is very complex and overlap. One of the efforts that can be used to degrade the connective tissue protein structures is to use agricultural waste products of fermentation results. One agricultural materials such as waste that is possible can be used as a source of carbohydrate is cassava (casapro)which is agro waste. This research result of industrial waste utilizing cassava starch by fermentation. Animals used were male duck and the treatment used is P0 without the addition of fermented cassava (casapro) in the ration and the addition of cassava fermentation treatment P1 (casapro) 5% in the ration. The results obtained during 1.5 months of maintenance are produced using fermentation of cassava in the ration effect on meat tenderness level based on the test panel and the use of meat tenderness. Keywords: duck meat, cassava (casapro), test panelists, meat tenderness.